New therapeutic strategies for combatting gastrointestinal toxicity. Issue 2 (June 2020) - Sylvester, Cyan L.; Anderson, Paul H.; Stringer, Andrea M.
Abstract : Purpose of review: An overwhelming majority of chemotherapy agents are known to cause gastrointestinal mucositis, an unwanted side effect of cancer treatment, for which no effective treatment currently exists. The pathological processes underlying the development of gastrointestinal mucositis are many and varied, with multiple pathways thought to be involved in initiation of inflammation and apoptosis. Physiological and or biochemical-based deficiencies, such as vitamin D deficiency and gut microbiome density and population, are also thought to have an impact on mucositis severity. Recent findings: Recent studies investigating inflammatory pathways, such as cytokines and apoptotic markers, do show that interleukin-blocking proteins alleviate symptoms of gastrointestinal mucositis. However, the effectiveness of these treatments varies depending on the type of anticancer agent administered, meaning blocking compounds may be limited in their application. Targeting the host's gut microbiome in preventing dysbiosis is also thought to be a potential avenue for exploration. The use of probiotic gut bacteria (i.e. Lactobacillus spp.), while beneficial in preventing chemotherapy radiotherapy-induced diarrhoea, does not seem to alleviate the physiological damage caused by gastrointestinal mucositis. Vitamin D has been widely shown to have a host of anti-inflammatory and immunomodulatory effects in the intestine, as well as anticancer properties and therefore, may reduce severity of gastrointestinal mucositis. Summary: While anti-inflammatory and antiapoptotic agents have shown promise in animal models of gastrointestinal mucositis, there is still no singular mechanism allowing for the development of a therapeutic drug to prevent or cure gastrointestinal injury. A greater insight into the exact mechanistic actions of both probiotics and vitamin D might reveal how to improve their use as therapeutic treatments for gastrointestinal mucositis.